Role of management ethics in promoting organizational loyalty-Field study at the General Company for Inland Transport in Latakia- (Journal of Hama University, 2022)
The study aimed at finding out the effect of management ethics in enhancing organizational loyalty in the general company for local transportation in Latakia. The research adopted the descriptive method. The sample consists of 35 questionnaires which have been distributed among the management staff (higher, intermediate and lower), and all of which have been returned. After examination, three questionnaires have been found invalid and 32 valid for utilization and study. The researcher has reached the following results:A mediocre moral relationship has been found between management ethics in all its dimensions (social responsibility, job dues, job duties and ethical environment) and organizational loyalty in the studied company, manifested through the workers carrying out the required task while still regarding the public interest, maintaining job discretion and adhering to rules and regulations regardless of personal considerations. It is also manifested through the workers' satisfaction with incentives and rewards they get while still committing to organization's message, principles and organizational culture, and holding public interest above everything else. In the light of these findings, the study has concluded with numerous recommendations, most importantly: development and establishment of principle of management ethics in Syrian work environment, including that of the studied company, through providing training courses that solidify ethical values, principles and standards in the mentality of the individual, the family and the society
Keywords: management ethics, social responsibility, job duties, job dues, ethical environment, organizational loyalty